Diagnostic utility of interferon gamma-induced protein 10 kDa in spontaneous bacterial peritonitis: single-center study. Issue 9 (September 2015) - Abdel-Razik, Ahmed; Mousa, Nasser; Elbaz, Sherif; Eissa, Mohamed; Elhelaly, Rania; Eldars, Waleed
Abstract : Background and aims: Spontaneous bacterial peritonitis (SBP) is an important cause of mortality and morbidity in cirrhotic patients with ascites. The diagnosis of SBP is mainly made on the basis of a polymorphonuclear leukocyte cell count exceeding 250/μl in ascitic fluid. However, this procedure is subjective. We aimed to evaluate serum and ascitic fluid interferon-γ-induced protein (IP-10) as accurate diagnostic markers for detecting SBP. Methods: A total of 425 consecutive patients with ascites were included. Serum and ascitic fluid of IP-10, tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) were measured using an enzyme-linked immunosorbent assay. Results: Patients were divided into an SBP group, including 61 patients, and a non-SBP group, including 364 patients. Serum and ascitic IP-10 were significantly higher in SBP patients than in patients without SBP (1855±825 vs. 955±510 pg/ml; P <0.001 and 2160±994 vs. 1110±623 pg/ml; P <0.001), respectively. There was a significant increase in both serum and ascitic levels of TNF-α and IL-6 in SBP patients than in patients without SBP. At a cut-off value of 1915 pg/ml, serum IP-10 had 91% sensitivity and 89% specificity for detecting SBP (area under the curve: 0.912). Also, at a cut-off value of 2355 pg/ml, ascitic IP-10 had 92.5% sensitivity and 87% specificity for detecting SBP (area under the curve: 0.943). Both were correlated with ascitic fluid proteins, polymorphonuclear count, TNF-α, and IL-6. Conclusion: Serum and ascitic IP-10, TNF-α, and IL-6 are significantly increased in SBP patients versus patients without SBP. Serum level of IP-10 is more specific and sensitive, such as ascites. Thus, it seems to represent a satisfactory diagnostic marker for the diagnosis of SBP.